Modeling of interfacial and bulk charge transfer in dye-sensitized solar cells. Issue 1 (1st January 2017) - Gong, Jiawei; Sumathy, K.; Zhou, Zhengping; Qiao, Qiquan
Abstract: A simple, first-principles mathematical model has been developed to analyze the effect of interfacial and bulk charge transfer on the power output characteristics of dye-sensitized solar cells (DSSCs). Under steady state operating conditions, the Butler-Volmer equation and Schottky barrier model were applied to evaluate the voltage loss at counter electrode/electrolyte and TiO2 /TCO interfaces, respectively. Experimental data acquired from typical DSSCs tested in our laboratory have been used to validate the theoretical J–V characteristics predicted by the present model. Compared to the conventional diffusion model, the present model fitted the experimental J–V curve more accurately at high voltages (0.65–0.8 V). Parametric studies were conducted to analyze the effect of series resistance, shunt resistance, interfacial overpotential, as well as difference between the conduction band and formal redox potentials on DSSCs' performance. Simulated results show that a "lower-limit" of shunt resistance (10 3  Ωcm 2 ) is necessary to guarantee a maximized efficiency. The model predicts a linear relationship between open circuit voltage (Voc ) and photoanode temperature (T) with a slope of −1 mV/°C, which is close to the experimental data reported in literature. Additionally, it is observed that a small value of overpotential (2.2 mV) occurs at the short-circuit condition (Jsc  = 10.5 mA/cm 2 ), which is in a close agreement with Volmer-Butler equation. This observation suggests that, compared to the maximum attainable voltage (700 mV), the overpotential values are small and can be neglected for platinum catalyst based DSSCs.